Quantitative 3D microscopy highlights altered von Willebrand factor α‐granule storage in patients with von Willebrand disease with distinct pathogenic mechanisms - Maurice Swinkels; Ferdows Atiq; Petra E. Bürgisser; Johan A. Slotman; Adriaan B. Houtsmuller; Cilia deHeus; Judith Klumperman; Frank W. G. Leebeek; Jan Voorberg; Arend Jan Gerard Jansen; Ruben Bierings (Research and Practice in Thrombosis and Haemostasis, 2021)
Abstract Background Platelets play a key role in hemostasis through plug formation and secretion of their granule contents at sites of endothelial injury. Defects in von Willebrand factor (VWF), a platelet α‐granule protein, are implicated in von Willebrand disease (VWD), and may lead to defective platelet adhesion and/or aggregation. Studying VWF quantity and subcellular localization may help us better understand the pathophysiology of VWD. Objective Quantitative analysis of the platelet α‐granule compartment and VWF storage in healthy individuals and VWD patients. Patients/Methods Structured illumination microscopy (SIM) was used to study VWF content and organization in platelets of healthy individuals and patients with VWD in combination with established techniques. Results SIM capably quantified clear morphological and granular changes in platelets stimulated with proteinase‐activated receptor 1 (PAR‐1) activating peptide and revealed a large intra‐ and interdonor variability in VWF‐positive object numbers within healthy resting platelets, similar to variation in secreted protein acidic and rich in cysteine (SPARC). We subsequently characterized VWD platelets to identify changes in the α‐granule compartment of patients with different VWF defects, and were able to stratify two patients with type 3 VWD rising from different pathological mechanisms. We further analyzed VWF storage in α‐granules of a patient with homozygous p.C1190R using electron microscopy and found discrepant VWF levels and different degrees of multimerization in platelets of patients with heterozygous p.C1190 in comparison to VWF in plasma. Conclusions Our findings highlight the utility of quantitative imaging approaches in assessing platelet granule content, which may help to better understand VWF storage in α‐granules and to gain new insights in the etiology of VWD.